Beschäftigungsentwicklung in Mitteldeutschland - Oliver Farhauer; Nadia Granato (Raumforschung und Raumordnung, 2006)
Comparing the labour market situation in East Germany shows that the employment volume in Sachsen-Anhalt has considerably declined whereas Thüringen has been performing much better. In our paper we analyse indicators relevant to employment development in both federal states (Bundesländer) using a benchmark approach. This reveals, that Thüringen is better equipped with regard to all indicators, the most pronounced differences being related to location factors and industry structure.